Semiotic of Female Masculinity in Videogame 'The Last of Us Part II' - Ginting, Riza Fahlevi; Zein, T. Thyrhaya; Perangin-Angin, Alemina Br. (Politeknik Harapan Bangsa Surakarta, 2022)
This study aims to interpret the signs of semiotics in the videogame The Last of Us Part II (TLOU Part II) which reflect the values of female masculinity initiated by Judith Halberstam (1998). Through Roland Barthes' (1977) semiotics theory, this study analyzes the denotative and connotative meanings of visual and verbal signs from the characters of the videogame TLOU Part II. The source of this research data comes from screenshots of the videogame walkthrough which is then focused into 12 data for qualitative descriptive analysis. The 12 data were analyzed for their denotative and connotative meanings, then followed by description of the female masculinity category initiated by Judith Halberstam. From this study it was found that the 2 characters studied, namely Ellie and Abby, each fulfill several of the 5 categories of female masculinity initiated by Judith Halberstam, namely Butch Realness, Femme Pretender, Male Mimicry, Fag Drag, and Denaturalized Masculinity through visual and verbal signs from video games. They each show the appearance, gesture, nature, culture, and ideology of female masculinity